APRIORI DATA MINING ALGORITHM TO DETERMINE RESTAURANT MENU ASSOCIATIONS - Riama Sibarani; Akmal Kurniawan (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2023)
Data mining is a process to dig or mine data from piles of data that have been for years. The pile of data that is considered waste can be used and used to provide an added value for the company. Some data mining algorithms include Apriori Algorithms. The Ariori algorithm is done by integrating the market basket analysis fiture and generating a list of menu packets from existing transactions into an application by analyzing a set of data stored in the transaction data. The combination of the menu on the transaction will result in the association menu which is a new menu package. This analysis is expected to be utilized by restaurant owners as a tool to support culinary business at Soto Ngawi Restaurant DepokJawa Barat.